DIPLOMASI KPOP SEBAGAI KEBIJAKAN LUAR NEGERI KOREA SELATAN TERHADAP INDONESIA - Aji Adira Fadia Putri Padmo; Achbil Khumaini Fajrin Muhammad; Adityamas Perdana Al-Hafidh; Muhammad Aria Senna (Jurnal PIR : Power in International Relations, 2021)
AbstractSouth Korea implements a soft power strategy, namely cultural diplomacy through the Korean Wave in its diplomatic relations with Indonesia. This strategy has get responded positively to relations between the two countries because the Korean Wave is now one of the most popular cultures in Indonesia. This paper aims to identify and analyze the interest of K-Pop cultural diplomacy on the cooperation between South Korea and Indonesia. The Korean Wave is part of Korean cultural diplomacy in Indonesia and has a great influence on bilateral relations between the two countries. South Korea has a great opportunity for the interest of the Indonesian people to K-Pop music because it can be used as a means of increasing closer cooperation with Indonesia, especially in the economic and socio-cultural fieldsKeywords: Cultural Diplomacy, South Korea, Indonesia, Korean Wave, Soft PowerAbstrakKorea Selatan menerapkan soft power strategy yaitu diplomasi budaya melalui Korean Wave dalam hubungan diplomatiknya dengan Indonesia. Strategi ini telah memberikan respon positif terhadap hubungan kedua negara karena Korean Wave kini menjadi salah satu budaya yang paling diminati oleh masyarakat Indonesia. Paper ini bertujuan untuk mengetahui dan menganalisis kepentingan diplomasi budaya K-Pop terhadap hubungan kerjasama Korea Selatan dan Indonesia.  Korean Wave yang merupakan bagian dari diplomasi budaya Korea di Indonesia dan memiliki pengaruh yang besar terhadap hubungan bilateral kedua Negara. Korea Selatan mempunyai peluang yang besar atas ketertarikan masyarakat Indonesia terhadap musik K-Pop karena hal tersebut dapat dijadikan sebagai alat untuk meningkatkan kerjasama yang lebih erat dengan Indonesia, khususnya di bidang ekonomi dan sosial budayaKata Kunci: Diplomasi Budaya, Korea Selatan, Indonesia, Korean Wave, Soft Power